The IFLA-Unesco Public Libraries Manifesto 2022: a key resource in support of public libraries - Omella, Ester (Anuario ThinkEPI, 2023)
We present an analysis of the most relevant points in the 2022 update of The IFLA-Unesco Public Libraries Manifesto 2022. The background of the 1994 manifesto is detailed, exploring its impact on library development and how the 2022 version strengthens values centered on inclusivity, civic participation, and community function. As examples of these focal points, the connection of the new manifesto text with current challenges for public libraries is highlighted: literacy skills, universal access to knowledge, the digital divide, social cohesion, citizen participation, employment inclusion, and information literacy. Finally, the implementation of the manifesto is addressed, urging national library associations to disseminate it. Available tools, such as the implementation decalogue, translations, an “easy reading” version of the manifesto, and all other tools from the toolkit, are presented for professionals, considering their implementation in different countries.
Keywords: IFLA-Unesco Public Library Manifesto 2022; Public libraries; Library development; Reading competency; Digital divide; Social cohesion; Citizen participation; Labor inclusion; Information literacy; Sustainable development